Short Communication: Microscopic decay pattern of yellow meranti caused by white-rot fungus Phlebia brevispora - ERWIN ERWIN (Biodiversitas Journal of Biological Diversity, 2016)
Erwin. 2016. Microscopic decay pattern of yellow meranti (Shorea gibbosa) wood caused by white-rot fungusÂ Plebia brevispora. Biodiversitas 17: 417-421. The anatomical changes of wood decaying by white-rot fungus Phlebia brevispora could provide the basis for evaluating and analysis of decay on yellow merantiÂ (Shorea gibbosa) heartwood. By using soil-block test procedure of JIS K-1571 and microscopic analysis, a progressive decay in vitro of S. gibbosa wood caused by P. brevispora was well characterized.The percentage of wood weight loss was ranged from 0.91% to 12.34%in 2-12 weeks' incubation. On the first 6 weeks of incubation of S. gibbosa infected with P. brevispora, the early stages decay, in which pit erosion and slight erosion of cell walls facilitated by hyphal spreading among cells. The intermediate decay features of numerous and conspicuous holes as well as erosion troughs in cell walls were found after 8 weeks' incubation. Furthermore, complete degradation of wood cell components, defined as the advanced stage of decay, was found in some areas of wood after 12 weeks' incubation. The pattern of wood decay was similar to those of the decayed xylem of S. gibbosa stem canker in field conditions.